2010
DOI: 10.3138/physio.62.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Practice Guidelines for Assessing Pain in Older Persons with Dementia Residing in Long-Term Care Facilities

Abstract: Purpose: Frail patients with dementia most frequently present with musculoskeletal pain and mobility concerns; therefore, physiotherapy interventions for this population are likely to be of great benefit. However, physiotherapists who work with older adults with dementia confront a considerable challenge: the communication impairments that characterize dementia make it difficult to assess pain and determine its source. For an effective physiotherapy programme to be implemented, valid pain assessment is necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 64 publications
1
45
0
2
Order By: Relevance
“…After each stimulus the subject was asked to rate the pain on a horizontally held colored analog scale (CAS), which is the pain rating tool recommended in patients with mild to moderate dementia. 14,15 The participants' ability to understand the scale had been tested at baseline and all were able to understand and explain the scale correctly.…”
mentioning
confidence: 99%
“…After each stimulus the subject was asked to rate the pain on a horizontally held colored analog scale (CAS), which is the pain rating tool recommended in patients with mild to moderate dementia. 14,15 The participants' ability to understand the scale had been tested at baseline and all were able to understand and explain the scale correctly.…”
mentioning
confidence: 99%
“…Weiner et al (1998) evaluated a numeric 0-10 pain scale; they found that older people with dementia who had major difficulties comprehending the scale tended to have MMSE scores closer to 13/30. Although MMSE scores can be used to determine the likelihood that self-reports of pain will be valid, it has been recommended that self-report measures always be attempted, regardless of the level of cognitive functioning (AGS, 2002;Hadjistavropoulos et al, 2007), because there are patients with low MMSE scores who can self-report pain (Hadjistavropoulos et al, 2010).…”
Section: Self-report Of Pain Intensitymentioning
confidence: 99%
“…When gathering self-report from older adults, providers should prompt simple and concrete questions (eg, “Does this hurt?”). 27 A common mistake made by providers when obtaining self-report is to ask “How are you doing?” or “Are you comfortable?” to solicit a response about pain. Questions about general well-being should not be substituted for pain assessment because these may elicit socially desirable answers and may not elicit any information about pain.…”
Section: Pain Assessmentmentioning
confidence: 99%
“…Assessment completed over time should use the same pain self-report tool and assessor when possible, and conduct pain assessment under similar situations (eg, during movement). 27 Reassessment should always occur: Upon transitions of care/settings—discharge and admissionAfter initial report of pain, regardless of intervention administrationAt each new report of pain (eg, breakthrough pain)After any intervention (pharmacologic, including analgesic trials in nonverbal older adults, and nondrug) has been provided to determine efficacy in reducing pain intensity and/or improving pain-related disability. If a medication is given, reassess at predetermined intervals: (1) at the onset of action of analgesic effect, (2) during the peak analgesic effect, and (3) at the time when medication levels are lowest (ie, generally 4–6 hours after administration).…”
Section: Pain Reassessmentmentioning
confidence: 99%